Fluorescence study on interactions of alpha-crystallin with the molten globule state of 1, 4-beta-D-glucan glucanohydrolase from thermomonospora sp induced by guanidine hydrochloride - Jagtap, Sharmili; Rao, Mala (Journal of Fluorescence, 2009)
In this paper, the interaction between alpha- crystallin and molten globule structure of 1,4-beta-D-Glucan Glucohydrolase (TSC) from an alkalothermophilic Thermomonospora sp. was investigated mainly by fluorescence quenching spectra, circular dichroism and three dimensional fluorescence spectra under simulative physiological conditions. Denaturation studies using GdnCl indicated that TSC folds through a partially folded state that resembles molten globule at 1.8 M GdnCl. The chaperone activity of alpha- crystallin was employed to study refolding of TSC. Here we studied the refolding of GdnCl denatured TSC from its molten globule state (TSC-m complex) in the presence and absence of alpha-crystallin to elucidate the molecular mechanism of chaperone-mediated in vitro folding. Our results, based on intrinsic tryptophan fluorescence and ANS binding studies, suggest that alpha-crystallin formed a complex with a putative intermediate molten globule - like intermediate in the refolding pathway of TSC. Reconstitution of the active TSC was observed on cooling the alpha-crystallin aEuro cent TSC -m complex to 4A degrees C. Addition of alpha-crystallin to the molten globule - like intermediate of TSC (TSC-m complex) complex initiated the refolding of TSC with 69 % recovery of the biological activity of the enzyme.
Keywords: ANS; Cellulase; Guanidine hydrochloride; Protein folding